PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Fiqria, Adilla; Sembiring, Seniwati; Pasaribu, Aria Masdiana (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2024)
This study This study aims to determine how a company's capital structure, growth and profitability impact its value on the Indonesian Stock Exchange from 2018 to 2020. This study looks at 27 companies and 17 companies as a sample. Data were processed using the spss 22 program. Data were examined using the coefficient of determination (R2), partial test (t), and linear regression with two lines. To find out how the independent variable influences the dependent variable in terms of the level of prosperity, a hypothesis test is carried out.